Omri van Israel: 'n Poging tot historiese rekonstruksie - J A Burger (Acta Theologica)
Historians usually use the Old Testament as their source of information in writing contemporary works on the history of ancient Israel. This information is usually merely paraphrased in writing a history of Israel, in spite of the non-primary historical and rather ideological character of the Old Testament. The application of Biblical material about Omri and his house in modern history books is no exception: Information extracted from the Old Testament enjoys preferential status in spite of the fact that extra-Biblical information on Omri also exists, as seen in the Mesha inscription as well as in Assyrian inscriptions.